THE RESTITUTION IN HUMAN TRAFFICKING LAW ENFORCEMENT IN RELATION TO VICTIM PROTECTION - Christina Maya Indah Susilowati (UNISSULA, 2022)
This is a general policy in the form of restitution or compensation from the criminal to the victim of human trafficking crime which becomes a parameter of victim's right fulfilment. The weakness in its formulation leads to lack of firmness of its implementation. In this writing I will make a theoretical study related to restitution law structure for human trafficking victims. This research jurisdically studied about the non-clarity of the policies related to restitution. The method used in this research is law research assisted by library study & evaluation to restitution policy making in human trafficking law enforcement. This research is important because human trafficking is now becoming a trasnational crime which is well structured & sistematically arranged. Human trafficking gives great advantage to the criminal doing it. It is because the victims become a never ending commodity. Some considerations about restitution policy, have negated that human trafficking victims are vulnerable to have a secondary victimization risk. They come face to face with this risk when they deal with the operation of criminal laws, because the law has not fully accomodated the victim's right. That's why we need a legal form in having a victim based approach restitution.